The Cross-Links of Endoplasmic Reticulum Stress, Autophagy, and Neurodegeneration in Parkinson’s Disease - Ren, Haigang; Zhai, Wanqing; Lu, Xiaojun; Wang, Guanghui (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is the most common neurodegenerative movement disorder, and it is characterized by the selective loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc), as well as the presence of intracellular inclusions with α-synuclein as the main component in surviving DA neurons. Emerging evidence suggests that the imbalance of proteostasis is a key pathogenic factor for PD. Endoplasmic reticulum (ER) stress-induced unfolded protein response (UPR) and autophagy, two major pathways for maintaining proteostasis, play important roles in PD pathology and are considered as attractive therapeutic targets for PD treatment. However, although ER stress/UPR and autophagy appear to be independent cellular processes, they are closely related to each other. In this review, we focused on the roles and molecular cross-links between ER stress/UPR and autophagy in PD pathology. We systematically reviewed and summarized the most recent advances in regulation of ER stress/UPR and autophagy, and their cross-linking mechanisms. We also reviewed and discussed the mechanisms of the coexisting ER stress/UPR activation and dysregulated autophagy in the lesion regions of PD patients, and the underlying roles and molecular crosslinks between ER stress/UPR activation and the dysregulated autophagy in DA neurodegeneration induced by PD-associated genetic factors and PD-related neurotoxins. Finally, we indicate that the combined regulation of ER stress/UPR and autophagy would be a more effective treatment for PD rather than regulating one of these conditions alone.